Smart Tourism Implementation: Tourism Management During The Covid-19 - Fitri Widiastuti; Idham Khalik; Sylvia Kartika Wulan Bhayangkari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Indonesia's tourism sector can be said to be superior to other countries, one of which is in Kerinci Regency, Jambi Province. This district made a breakthrough in creating a new environment for the world of tourism through smart tourism. Smart Tourism is a pillar of a smart city and an important element of a smart economy. This platform integrates the role of information technology in providing information services on the diversity of tourism offered, cultural, religious, heritage, culinary, and natural tourism for visiting tourists and reviving tourism which had been halted due to the COVID-19 pandemic. This study aims to see the application of smart tourism in tourism management in Kerinci Regency and are there any factors behind the local government, tourism managers in implementing smart tourism. Qualitative descriptive research design. The results obtained by local governments have collaborated with stakeholders, investors, financial institutions, MSMEs, communities around destinations to take long-term policies through